Отступления от нормы и их отражение в памятниках нормативного характера: на примере правил Ужгородского Псевдозонара XVII в. - Šašerina, Svetlana (Studia Rossica Posnaniensia, 2024)
Christian doctrine clearly regulates a person’s daily life, relationships with others, and behavior even down to eating. Breaking the commandments is considered a sin, and overcoming one’s own weakness leads to the improvement of man and bringing him closer to God, which is ultimately the goal of every Christian’s life. On the material of Cyrillic monuments of written texts of a teaching character, we will consider how the deviation from the norms of Christian morality and violation of the rules of doctrine are reflected in sermons. The sermon as a non-canonical, free genre is interesting for the study of the human value system; it is in the texts of sermons that one can find a reaction to socially significant events. In the article we will trace what sins are mentioned in sermons, what methods of overcoming them are suggested, and what values are emphasized as the main ones. We will conduct this study on the material of the sermons that are part of the Uglian didactical gospel, the didactical gospel of Clement Bukowski, and some other collections. To overcome sin, the Church used not only teachings, but also a collection of laws, the distinctive feature of which was the indication of punishment (penitentia) for the violation of this or that regulation. It should be noted that the various punishments were not physical, but spiritual (e.g. excommunication from the sacrament of confession and communion for a certain period of time, strict fasts, and many others), and the main purpose of punishment was to correct the sinful nature of man and bring him closer to God.